The Effect Of Milenial Generation Characteristics Of Job Satisfaction Relations And Employee Engagement - Alfatih Sikki Manggabarani; Faisal Marzuki; Mahendro (Yayasan Ilomata, 2020)
This research is a quantitative study that aims to determine the Millennial Generation Characteristics of Employee Engagement. The population in this study The study was conducted by taking samples of Millennials who are actively working at Micro Finance companies with a total of 150 respondents. The sample size was taken as many as 150 respondents, with probability sampling methods especially simple random sampling. Data collection was carried out through questionnaires. The analysis technique used is the PLS (Partial Least Square) analysis method. The results of this study indicate that the value of R- Square (R2) Employee Engagement is 0.786 and Employee Satisfaction is 0.647 thus indicating that the contribution of Grit, Worklife Balance, and Jon Resources variables to Employee Engagement and Employee Satisfaction are 0.786 or 78.6% and 0.647 or 64.7%. And the rest is influenced by other factors not examined.